The Study of Evangelicalism Limits and Potential of Emic and Etic Perspectives on a Growing Field of Research - Ehmann, Matthias 1987- (2024)
Vorliegender Artikel stellt neue Diskurse in der Evangelikalismusforschung im deutschen Sprachraum vor. Im Fokus sind unterschiedliche Sichtweisen und Standpunkte im schöpferischen Spannungsfeld zwischen Theologie und Religionswissenschaft. Nachgezeichnet wird die von angelsächsischen Beiträgen dominierte Forschungsgeschichte der evangelikalen Bewegung unter Berücksichtigung ausgewählter deutschsprachiger Veröffentlichungen. Diese werden dann in Kontrast gesetzt zu Gegenwartsmeinungen aus dem Bereich der deutschsprachigen Religionswissenschaft. Der Artikel fragt nach weitergehenden Perspektiven, die die Dichotomie zwischen emischen Innenorientierungen und etischen Außenorientierungen in der Forschungsperspektive überwinden, wie sie oft in der deutschsprachigen Evangelikalismusforschung vorzufinden sind.
This article introduces new discourses on the study of evangelicalism and the evangelical movement in German-speaking areas. Its focus is on the different perspectives and positions in the creative field of tension between theology and religious studies. The article traces the history of research into evangelicalism, which is dominated by Anglo-Saxon contributions, as well as other theological voices in Germany. This research tradition is contrasted with current opinions from the field of religious studies in the German-speaking world. The article asks for further perspectives that go beyond the divide between the emic and etic discourses as they are frequently found in German-language research on evangelicalism.
Keywords: Evangelical movement; Emic; etic; Evangelicalism; Intercultural Theology; new evangelicals; Religious Studies; revivalist Protestantism